METHODOLOGICAL PRINCIPLES OF DEVELOPING A COMPREHENSIVE PLAN FOR SPATIAL DEVELOPMENT OF THE TERRITORIAL COMMUNITY AREA - Dudych Г.; Dudych Л. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
The study proves that a comprehensive plan for spatial development of the area of territorial community significantly simplifies and speeds up implementation of the project decisions, because its main purpose is to substantiate the future needs and determine predominant directions of the area use considering the national, public and private interests, establishing restrictions on their planning, building or other use. It is justified that organization and development of the community area should be based on a set of project decisions of a comprehensive spatial development plan, which identifies the most rational distribution of the area, types and intensity of economic activity, mutual placement of production and non-production objects, engineering and transport communications, etc. The study presents the main stages of developing a comprehensive plan for spatial development of the area of the territorial community. Such plan provides information on the current use of the territory, which allows to analyze, identify problems, and propose ways of territorial development of the community. The proposed planning solutions on the functional purpose of the area, organization of engineering and transport infrastructure, engineering preparation and improvement, protection of the territory from dangerous natural and anthropogenic processes, protection of the natural environment, protection and preservation of immovable objects of cultural heritage and archaeological monuments are described in the project plan that is subject to public discussion.